Improving College Students' English Phoneme Acquisition Performance through FiF Oral Training System-Assisted Blended Learning - Wang, Xiaoyun; Julian Robillos , Roderick (Forum for Linguistic Studies, 2025)
This study investigated the effectiveness of blended learning using the FiF Oral Training App on English phoneme acquisition specifically fluency, intelligibility, articulation, and rhythm, and explored students' satisfaction and attitudes toward pronunciation learning. A quasi-experimental design was employed with two intact classes of Primary English Education freshmen at Lijiang Normal University: an experimental group (n = 40) using the FiF App and a control group (n = 40) receiving conventional instruction. Both groups were comparable in prior English performance. Quantitative data from pre-and post-tests and pronunciation learning questionnaires were analyzed using descriptive and inferential statistics. The control group showed modest gains: fluency increased from 6.45 to 7.59, intelligibility from 6.21 to 7.35, articulation from 6.34 to 7.26, and rhythm from 6.28 to 7.35 (all at p < 0.001). The experimental group demonstrated superior improvements: fluency from 5.83 to 7.86, intelligibility from 5.76 to 7.66, articulation from 5.90 to 7.83, and rhythm from 5.74 to 7.63. The experimental group outperformed the control group across all measures, with articulation reaching statistical significance (p = 0.022).Both groups reported positive attitudes toward pronunciation learning. However, the experimental group expressed stronger agreement regarding the importance of pronunciation (M = 1.23 vs. 1.41) and perceived greater support from the learning environment (M = 1.35 vs. 1.53). Findings suggest that integrating AI-based tools like the FiF App enhances articulation and fosters positive learner attitudes, indicating the pedagogical value of blending technology with pronunciation instruction.